Papers Martin Luther Haynie - Haynie, Martin Luther
Account book kept by Haynie describing travels including voyages between the cities of Hamburg, Germany, and Baltimore, Maryland, and between New York state and Liverpool, England. Documents expenses related to his travels and to his slave, Henny. Includes a handwritten description and partial transcript.
Transcript, in part.
Slaveholder of Somerset County, Md.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection
Keywords: Slavery -- United States; Slaves -- Maryland; Voyages and travels; Baltimore (Md.) -- Description and travel; Hamburg (Germany) -- Description and travel; Liverpool (England) -- Description and travel; New York (State) -- Description and travel; Somerset County (Md.) -- Social life and customs; Slaveholders